Associations of perceived drinking motives of parents and friends on adolescents' own drinking motives. Issue 1 (2nd January 2021) - Cloutier, Renee M.; Zamboanga, Byron L.; Kearns, Nathan; Guillot, Casey R.; Blumenthal, Heidemarie
Abstract: Adolescents form perceptions of why their parents and friends drink alcohol that may impact adolescents' own drinking motives. This study tested whether perceived drinking motives of parents and friends are associated with adolescents' own drinking motives. Participants included community-recruited adolescents 14–17 years ( N  = 105; 63.8% female) who drank alcohol in the past year. Perceived parent and friend motives both related to adolescent drinking motives at the bivariate level; however, only friend motives remained statistically significant in the final hierarchical regression models controlling for relevant covariates (e.g., alcohol frequency). Findings support a social-cognitive modeling pathway in the development of adolescents' own drinking motives and highlight the perception of why others drink as a potential intervention target.